Skyrmions and composite fermions in the limit of vanishing Zeeman energy - Nicholas, R; Leadley, DR; Maude, D; Portal, J; Harris, J; Foxon, C (1998)
We describe the properties of a strongly interacting two-dimensional (2D) electron gas in high magnetic fields whose properties can be described in terms of the formation of composite fermions at fractional Landau level occupancy. For a Landau level occupancy nu = 1 the excitations correspond to spin waves for high g-factors and magnetic fields, but when the g-factor is reduced close to zero by the use of hydrostatic pressure there is strong evidence for the formation of skyrmions. Studies of composite fermions in the limit of vanishing Zeeman energy also suggest that skyrmionic excitations can occur for composite fermions.